2021
DOI: 10.1073/pnas.2015685118
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal and reversible control of neuronal signaling and behavior by midinfrared stimulation

Abstract: Various neuromodulation approaches have been employed to alter neuronal spiking activity and thus regulate brain functions and alleviate neurological disorders. Infrared neural stimulation (INS) could be a potential approach for neuromodulation because it requires no tissue contact and possesses a high spatial resolution. However, the risk of overheating and an unclear mechanism hamper its application. Here we show that midinfrared stimulation (MIRS) with a specific wavelength exerts nonthermal, long-distance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
107
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 55 publications
2
107
0
4
Order By: Relevance
“…Actually, we noticed that RFNs in the THz group tend to generate more APs at higher current stimulation intensity ( Figure S4 L), although the statistics did not reach to significant difference. Interestingly, a recent work reported that midinfrared 53.6 THz (wavelength 5.6 μm) radiation with ∼110 μW/μm 2 density increases neuronal firing through voltage-gated potassium channel, by acting on resonance vibration of –C = O bonds at the potassium channel ( Liu et al., 2021 ). And this result is a non-thermal effect of midinfrared wave.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, we noticed that RFNs in the THz group tend to generate more APs at higher current stimulation intensity ( Figure S4 L), although the statistics did not reach to significant difference. Interestingly, a recent work reported that midinfrared 53.6 THz (wavelength 5.6 μm) radiation with ∼110 μW/μm 2 density increases neuronal firing through voltage-gated potassium channel, by acting on resonance vibration of –C = O bonds at the potassium channel ( Liu et al., 2021 ). And this result is a non-thermal effect of midinfrared wave.…”
Section: Discussionmentioning
confidence: 99%
“…Shape of AP strongly relate to membrane resistance, with decreased and increased resistance being respectively associated to narrower and broader AP (Volgushev et al, 2000; Hedrick and Waters, 2011). Membrane resistance and AP waveform are also very sensitive to change in temperature with increased and decreased temperature leading respectively to lower/narrower and higher/broader membrane resistance and AP (Goldin and Mindin, 2017, Liu et al, 2021, Hedrick and Waters, 2011; Volgushev et al, 2000). Therefore, it cannot be excluded that the observed effect on AP waveform as a thermal origin (Romanenko et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it cannot be excluded that the observed effect on AP waveform as a thermal origin (Romanenko et al, 2014). Recently, it was reported that midinfrared radiations also shorten AP by accelerating its repolarization, through an increase in voltage-gated potassium currents (Liu et al, 2021). Mechanisms of RF fields might differ from midinfrared radiation as they manifest predominantly by a stepper depolarisation phase.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there are rising evidence shed light on that mid-infrared stimulation (MIRS) with a specific wavelength could lead to dramatic changes: 1) neuronal firing . MIRS can exert non-thermal effects on ion channels, and lead to gain modulation of action potentials based on current injections in vitro brain slices (Liu, et al, 2021). MIRS can enhance neuronal spontaneous activities (Zhang, et al, 2021) and sensory responses (Tan, et al, 2021) in anesthetized animals.…”
Section: Introductionmentioning
confidence: 99%